2013
DOI: 10.1371/journal.pone.0064627
|View full text |Cite
|
Sign up to set email alerts
|

Missense Mutation in CAPN1 Is Associated with Spinocerebellar Ataxia in the Parson Russell Terrier Dog Breed

Abstract: Spinocerebellar ataxia (SCA) in the Parson Russell Terrier (PRT) dog breed is a disease of progressive incoordination of gait and loss of balance. Clinical signs usually become notable between 6 and 12 months of age with affected dogs presenting with symmetric spinocerebellar ataxia particularly evident in the pelvic limbs. The degree of truncal ataxia, pelvic limb hypermetria and impaired balance is progressive, particularly during the initial months of disease. A certain degree of stabilisation as well as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 40 publications
5
64
1
Order By: Relevance
“…6,8 In knockdown mice, hypomyelination in the spinal cord with severe spongiform vacuolation, axonal swelling and degeneration is also described. 46 To the author's knowledge, there are currently no pathological reports available of humans with SeSAME/EAST syndrome.…”
Section: Kcnj10 Variant Causes Sesame/east In Malinois Dogsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8 In knockdown mice, hypomyelination in the spinal cord with severe spongiform vacuolation, axonal swelling and degeneration is also described. 46 To the author's knowledge, there are currently no pathological reports available of humans with SeSAME/EAST syndrome.…”
Section: Kcnj10 Variant Causes Sesame/east In Malinois Dogsmentioning
confidence: 99%
“…Until now, only the KCNJ10 c.627C4G (p.(Ile209Met)) variant has been reported to be associated with spinocerebellar ataxia and myokymia, seizures or both (SAMS) in certain Terrier breeds. 6,7 In addition, Forman et al 8 reported that the CAPN1 c.344G4A (p.(Cys115Tyr)) variant is strongly associated with late-onset ataxia in Parson Russell Terriers, suggesting that CAPN1 may represent a novel candidate gene for ataxia in humans. According to OMIA there are no spontaneous disease causing variants in KCNJ10 described in other species.…”
mentioning
confidence: 99%
“…Spinocerebellar degeneration has been reported in Brittany Spaniels, 39 Jack Russell Terriers, Parson Russell Terriers, [6][7][8][9] and Smooth-haired Fox Terriers (also known as Russell Terrier Group) (see Table 1). 40,41 Brittany Spaniels suffer from late-onset (5-10.7 years) spinocerebellar degeneration.…”
Section: Spinocerebellar Degenerationmentioning
confidence: 99%
“…This disease has been associated with a missense mutation in CAPN1. 9 The CAPN1 gene encodes an intracellular calcium-dependent cysteine protease called calpain 1. Although the exact function of calpain 1 is unknown, it is proposed to play a role in neuronal maintenance and remodeling; this represents a third disorder in which potential defects in disposal of proteins results in neuronal degeneration.…”
Section: Spinocerebellar Degenerationmentioning
confidence: 99%
See 1 more Smart Citation